Evelyn Wadsworth Symington collection of John Hay material - Symington, Evelyn Wadsworth, 1903-1972.
Correspondence, diaries, a speech, writings, poetry, newspaper clippings, and other papers by and about John Hay, Symington's grandfather. Individuals represented include Henry Adams, Alfred Austin, Philippe Bunau-Varilla, Lloyd Carpenter Griscom, Abraham Lincoln, Robert Todd Lincoln, William McKinley, John G. Nicolay, and William T. Sherman.
In part, positive photocopy.
Collector.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hay, John, -- 1838-1905.; Adams, Henry, -- 1838-1918.; Austin, Alfred, -- 1835-1913.; Bunau-Varilla, Philippe, -- 1859-1940.; Griscom, Lloyd Carpenter, -- 1872-1959.; Lincoln, Abraham, -- 1809-1865.; Lincoln, Robert Todd, -- 1843-1926.; McKinley, William, -- 1843-1901.; Nicolay, John G. -- 1832-1901.; Sherman, William T. -- 1820-1891.; Collectors